Islamic Theology and Philosophy: Studies in Honor of George F. Hourani By Michael E. Marmura (ed.). Albany: State University of New York Press, 1984. (American Journal of Islam and Society, 1992)
Michael Marmura, the editor of this volume, has brought to his readersa valuable collection of highly respected authors, from van Ess and Frank toAnawati in part one, and from Makarem, Nasr, and Mahdi to Shehadi in parttwo. Each contributor to this seventeen-essay volume is an authority on his/hertopic. Indeed, what we have here is a collection of essays in which by someof today 's most competent and respected lslamicists inform the readers of theresults of their scholarly research into various aspects of their discipline andthereby producing a resounding tribute worthy of a scholar of the stature ofGeorge Hourani, to whom the volume is dedicated.To be sure, not only is this work written by experts, but it is also meantfor the experts. The essays are thus quite naturally extremely narrow in scopeand perspective and are also self-contained and therefore independent of eachother. As a result, each essay is tightly packed, and reviewing this book wouldmean reviewing each essay separately. Alternatively, and this would be muchmore desirable, the reviewer can present a general account of the problematicsof Islamic theology and philosophy in which each contribution coheres to formsome kind of an overall picture. But, in fairness, this is the task of the editor,not of the reviewer. Thus one wonders why Marmura, given his standing inand familiarity with the field, did not write general introductory articles foreach of the volume's two sections: "Islamic Theology" and "Islamic Philosophy."For example, it is not clear to the reader as to how and in what way van Ess'spowerful analysis of a kalam anecdote is related to Frank's penetrating studyof the kalam doctrine of bodies and atoms. For the reader, unless he/shepossesses the same degree of expertise as the two authors, the only thing incommon between them is that they both talk about the mutakallimun. Similarly,in more general terms, the reader legitimately wonders if there are any broadconcerns, or if there are any shared methodological approaches, which bindall of those different Islamic philosophers whose thought forms the subjectmatter of the book's second part. These questions could have been dealt within an editorial panorama. Indeed, one may argue that a general account ispossible only after the basic data have been collected, and since much of theclassical literature of Islam still lies unstudied, a survey article would bepremature. But a survey need not be definitive - it can always be tentative ...